Innovation, path dependency and policy the Norwegian case - Fagerberg, Jan.; Mowery, David C.; Verspagen, Bart. (Oxford : Oxford University Press, 2009)
The concept of National Innovation Systems is well established in academic research and adopted by policymakers. Yet there are relatively few in-depth studies of individual national innovation systems. This text provides just that, a model for the application of the concept to an individual economy, that of Norway.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Technological innovations -- Government policy -- Norway; Technological innovations -- Economic aspects -- Norway